Biochemical properties of a novel cysteine protease of Plasmodium vivax, vivapain-4. - Byoung-Kuk Na; Young-An Bae; Young-Gun Zo; Youngchool Choe; Seon-Hee Kim; Prashant V Desai; Mitchell A Avery; Charles S Craik; Tong-Soo Kim; Philip J Rosenthal; Yoon Kong (Public Library of Science (PLoS), 2010)
Multiple cysteine proteases of malaria parasites are required for maintenance of parasite metabolic homeostasis and egress from the host erythrocyte. In Plasmodium falciparum these proteases appear to mediate the processing of hemoglobin and aspartic proteases (plasmepsins) in the acidic food vacuole and the hydrolysis of erythrocyte structural proteins at neutral pH. Two cysteine proteases, vivapain (VX)-2 and VX-3 have been characterized in P. vivax, but comprehensive studies of P. vivax cysteine proteases remain elusive.We characterized a novel cysteine protease of P. vivax, VX-4, of which orthologs appears to have evolved differentially in primate plasmodia with strong cladistic affinity toward those of rodent Plasmodium. Recombinant VX-4 demonstrated dual substrate specificity depending on the surrounding micro-environmental pH. Its hydrolyzing activity against benzyloxycarbonyl-Leu-Arg-4-methyl-coumaryl-7-amide (Z-Leu-Arg-MCA) and Z-Phe-Arg-MCA was highest at acidic pH (5.5), whereas that against Z-Arg-Arg-MCA was maximal at neutral pH (6.5-7.5). VX-4 preferred positively charged amino acids and Gln at the P1 position, with less strict specificity at P3 and P4. P2 preferences depended on pH (Leu at pH 5.5 and Arg at pH 7.5). Three amino acids that delineate the S2 pocket were substituted in VX-4 compared to VX-2 and VX-3 (Ala90, Gly157 and Glu180). Replacement of Glu180 abolished activity against Z-Arg-Arg-MCA at neutral pH, indicating the importance of this amino acid in the pH-dependent substrate preference. VX-4 was localized in the food vacuoles and cytoplasm of the erythrocytic stage of P. vivax. VX-4 showed maximal activity against actin at neutral pH, and that against P. vivax plasmepsin 4 and hemoglobin was detected at neutral/acidic and acidic pH, respectively.VX-4 demonstrates pH-dependent substrate switching, which might offer an efficient mechanism for the specific cleavage of different substrates in different intracellular environments. VX-4 might function as a hemoglobinase in the acidic parasite food vacuole, a maturase of P. vivax plasmepsin 4 at neutral or acidic pH, and a cytoskeleton-degrading protease in the neutral erythrocyte cytosol.